Assessment of Climate Change Impacts on Drought Characteristics and Trivariate Return Period Risks in Western Iran - Behnoush Farokhzadeh; Sepideh Chobeh; Rasool Imani (اکوهیدرولوژی)
Objective: This study investigates the impact of climate change on drought characteristics in western Iran by analyzing trends in drought intensity, duration, and magnitude. The research aims to assess future drought risks under different climate scenarios to support water resource management strategies.Method: Historical precipitation data (1966–2020) from six meteorological stations were analyzed using the Standardized Precipitation Index (SPI). Future climate projections were generated using the HadCM3 General Circulation Model (GCM) and downscaled with the LARS-WG model under SSP2-4.5 and SSP5-8.5 scenarios. Statistical trend analysis, probability distribution fitting, and copula functions were applied to evaluate the interdependence of drought characteristics and estimate joint return periods.Results: The findings indicate an increasing trend in drought severity, particularly in Hamedan and Saqez, with SSP5-8.5 showing the most extreme conditions. Drought intensity and duration are projected to increase, with prolonged dry periods becoming more frequent. Joint return periods suggest that severe drought events, previously occurring every 20 years, may now happen every 10 years.Conclusions: Climate change is intensifying drought risks in western Iran, requiring urgent adaptation strategies. Copula-based analysis highlights stronger dependencies between drought characteristics, increasing the likelihood of extreme events. Effective water management policies, including improved storage and irrigation systems, are essential to mitigate future drought impacts.